The D-day project: reaching peak performance during the Olympic Games - Bosquet, Laurent (Réflexions Sport, 2024)
The purpose of the D-day program was to optimize the final three weeks leading up to the Paris 2024 Olympic Games, ensuring that France’s swimmers reached their peak performance during the competition. The program focused on two key areas: training load parameters and recovery methods, particularly those influencing sleep quality. The first phase, spanning two years, involved experimental studies that tested various strategies to refine their application. The second two-year phase implemented these strategies with members of the French national team, gradually establishing individualized plans. A unique aspect of this project, with potential applicability to other sports, was its collaborative approach. It was co-developed by scientists from the consortium, the swimmers’ coaches, and a representative from the national technical direction, specifically the federation’s scientific director. The strategy was based on: 1) existing evidence and findings from the project’s first phase, 2) the unique biological, psychosocial, environmental, and sporting characteristics of each swimmer, and 3) evaluations conducted before various national and international competitions, allowing for gradual adjustments aimed at peak performance in 2024. The results speak for themselves: fourteen finalists, three gold medals, seven silver medals, and two bronze medals at the European Championships in Rome (2022); seven finalists, one gold medal, and two bronze medals at the World Championships in Fukuoka (2023); and eleven finalists with one bronze medal (shared by two swimmers) at the Paris 2024 Olympic Games.